Microwave-vapor heat disinfestation on oriental fruit fly eggs in mangoes - J. Varith (2018)
The objective of this research was to develop a microwave-vapor heat treatment (MW-VHT) for mangoes (Mangifera indica L.) cv. Namdokmai Si Thong to disinfest the oriental fruit fly, Bactrocera dorsalis (Hendel). The mortality of oriental fruit fly eggs and quality acceptability characterized by thermal-death-time and thermal-quality-time overlay plots were initially obtained by hot-water immersion. Two treatments within a range of acceptable quality were selected for inoculation experiments to confirm MW-VHT process. The acceptable range was temperature ranging from 46 to 55C with time ranging from 2 to 20 min. The MW-VHT using microwave for preheating followed by vapor for holding processes effectively disinfested oriental fruit fly eggs. Changes in physiochemical properties of mangoes, e.g., color, titratable acid (TA), total soluble solid (TSS), TSS/TA and firmness, of MW-VHT-treated mangoes were not significantly different (P > 0.05) from physiochemical properties of the nontreated mangoes. MW-VHT resulted in less heat damage of mangoes than conventional vapor heat treatment (VHT) and shortened process time more than 90% during the preheating period. MW-VHT also retained equivalent or better lethality of oriental fruit fly eggs than did conventional VHT. © 2007, Blackwell Publishing.